Beta-alanine supplementation in patients with COPD receiving non-linear periodised exercise training or neuromuscular electrical stimulation: protocol of two randomised, double-blind, placebo-controlled trials - Martijn A Spruit; Emiel F M Wouters; Eline bij de Vaate; Peter Klijn; Frits M E Franssen; Wim Derave; Chris Burtin; Florence N Schleich; Roy Meys; Anouk A F Stoffels; Jana de Brandt; Hieronymus W H van Hees; et al. (BMJ Open)
Introduction Exercise intolerance is common in patients with chronic obstructive pulmonary disease (COPD) and, although multifactorial, it is largely caused by lower-limb muscle dysfunction. Research has shown that patients with severe to very severe COPD have significantly lower levels of muscle carnosine, which acts as a pH buffer and antioxidant. Beta-alanine (BA) supplementation has been shown to consistently elevate muscle carnosine in a variety of populations and may therefore improve exercise tolerance and lower-limb muscle function. The primary objective of the current studies is to assess the beneficial effects of BA supplementation in enhancing exercise tolerance on top of two types of exercise training (non-linear periodised exercise (NLPE) training or neuromuscular electrical stimulation (NMES)) in patients with COPD.Methods and analysis Two randomised, double-blind, placebo-controlled trials have been designed. Patients will routinely receive either NLPE (BASE-TRAIN trial) or NMES (BASE-ELECTRIC trial) as part of standard exercise-based care during their 8-to-10 week pulmonary rehabilitation (PR) programme. A total of 222 patients with COPD (2×77 = 154 patients in the BASE-TRAIN trial and 2×34 = 68 patients in the BASE-ELECTRIC trial) will be recruited from two specialised PR centres in The Netherlands. For study purposes, patients will receive 3.2 g of oral BA supplementation or placebo per day. Exercise tolerance is the primary outcome, which will be assessed using the endurance shuttle walk test (BASE-TRAIN) or the constant work rate cycle test (BASE-ELECTRIC). Furthermore, quadriceps muscle strength and endurance, cognitive function, carnosine levels (in muscle), BA levels (in blood and muscle), markers of oxidative stress and inflammation (in blood, muscles and lungs), physical activity and quality of life will be measured.Ethics and dissemination Both trials were approved by CMO Regio Arnhem-Nijmegen, The Netherlands (NL70781.091.19. and NL68757.091.19).Trial registration number NTR8427 (BASE-TRAIN) and NTR8419 (BASE-ELECTRIC).